Corporate and Individual Influences on Managers' Social Orientation - Marz, Joachim W. (Journal of business ethics, 2003)
This paper reports research on the influence of corporate and individual characteristics on managers' social orientation in Germany. The results indicate that mid-level managers expressed a significantly lower social orientation than low-level managers, and that job activity did not impact social orientation. Female respondents expressed a higher social orientation than male respondents. No impact of the political system origin (former East Germany versus former West Germany) on social orientation was shown. Overall, corporate position had a significantly higher impact on social orientation than did the characteristics of the individuals surveyed.